Gambaran Klaim Pelayanan Dialisis di Rumah Sakit dan Rekomendasi Kebijakan di Level Daerah: Studi Kasus Kota Pematangsiantar - Hasibuan, Syarif Rahman; Prasetyo, Chandra Istanti; Darmawan, Ede Surya; Permanasari, Vetty Yulianty (Jurnal Ekonomi Kesehatan Indonesia, 2024)
Chronic kidney disease is a global health issue affecting more than 10% of the world's population and poses a significant disease burden, especially in developing countries. In Indonesia, the National Health Insurance program (JKN) has enabled access to dialysis care for patients with chronic kidney failure, but it also presents challenges in sustaining financing. This study aims to analyze the trends in dialysis service claims in Pematangsiantar City during the period from 2017 to 2022 and project the service needs until 2025. The research design is descriptive-analytic, using claim data from BPJS Health related to dialysis procedures. Analysis is conducted using polynomial trends to identify historical patterns and future projections. The results show that the average annual cost of dialysis service claims in Pematangsiantar City is 85 billion rupiah. There was an annual increase in visits and claims costs by 25.56% and 23.52%, respectively. In 2021, dialysis visits surged by 91.6%, with claim costs reaching Rp128.2 billion. Projections up to 2025 indicate a significant upward trend, with an estimated number of visits approaching 350,000 in that year. The study's conclusions emphasize the importance of maintaining sustainable health financing through the JKN program and adjusting dialysis service capacity according to demand to prevent over- or undersupply. Additionally, primary prevention efforts through health education and early detection of kidney disease should be prioritized to reduce the number of new patients requiring dialysis.